Proximate composition of different mushroom varieties and effect of UV light exposure on vitamin D content in Agaricus bisporus and Volvariella volvacea - Ahlawat, O P; Manikandan, K; Singh, Manjit (Mushroom Research, 2019)
The fruit bodies of four mushroom varieties viz., Agaricus bisporus, Pleurotus eous, Volvariella volvacea and Lentinula edodes were analysed for their proximate composition. V. volvacea with 38.10% was richest in protein, followed by A. bisporus, P. eous and L. edodes. A. biporus was found to contain higher levels of fat, vitamin D, sodium, potassium and selenium compared to other three mushrooms. However, it had relatively low potassium: sodium ratio. P. eous was rich in iron and zinc and it was nearly two folds higher than other mushrooms. L. edodes was found to contain lowest level of both potassium and sodium but potassium: sodium ratio was highest in this mushroom along with manganese. Ultraviolet-C (254 nm) exposure of the fruiting bodies of A. bisporus and V. volvacea for different durations revealed nearly 2-4 folds enhancement in vitamin-D content in these two mushrooms. Exposure time of 15 and 45 min was found optimum for enhancement in vitamin D content in strain DMR3 and Horst U3 strain of A. bisporus, respectively, while it was 30 min for V. volvacea.Â